Effect of ozone fumigation on Storage ability of three date palm Phoenix dactylifera L cultivars - Hamza, Hamza Abbass (Basrah Journal Of Date Palm Research, 2024)
The study was conducted in the Care and Storage Laboratory of the Department of Horticulture and Landscape Design, College of Agriculture, to investigate the effect of ozone fumigation on the storage capacity of three date palm cultivars: Barhi, Khadrawi, and Habsi. The fruits were treated with ozone gas emitted from an ozone generator at a concentration of 5 ppm for durations of (0, 2, and 4) hours. The fruits were then packed in polyethylene bags with three replicates per sample. The experiment was designed using a Completely Randomized Design (CRD), and means were compared using the LSD test at a significance level of 0.05. The results showed that the Habsi cultivar recorded the lowest infection rate, the lowest weight loss percentage, and the highest total soluble solids (TSS) percentage (7.00%, 0.174%, and 76.10%, respectively). The results also indicated that treating fruits with ozone for 4 hours was superior in reducing infection rates, minimizing weight loss, and maintaining the TSS percentage, which were (1.56%, 0.129%, and 75.64%, respectively). Additionally, the results revealed that infection rates, weight loss percentages, and TSS percentages increased with prolonged storage duration.